Micro electro discharge machining of nonconductive ceramic: the issue of spalling - Ali, Mohammad Yeakub; Sabur, Abdus; Maleque, Md. Abdul (Science Publishing Corporation Inc, 2018)
Nonconductive ceramic materials are used in many engineering applications such as car brake, turbine blade, and hip-bone replacement because of its high dimensional accuracy, corrosion and wear resistant, and biocompatibility. These materials are usually processed with diamond grinding and limited laser applications such as cutting, drilling and scribing. Specific shapes and profiles are still difficult and costly to machine using these processes. Electrical discharge machining (EDM), extensively used for various shapes and profiles on con-ductive materials having minimum electrical conductivity of 0.10 S.cm-1. It is not directly applicable on nonconductive ceramic materi-als due to its very low electrical conductivity (<10-10 S.cm-1). However, recently EDM is used on nonconductive materials with the aid of assisting electrode to initiate the spark between conductive tool electrode and nonconductive workpiece. The available material re-moval models of EDM are based on single spark erosion with uniform melting and vaporization of workpiece materials. However, in EDM of nonconductive ceramics, material removal is not uniform because of random spalling due to alternating thermal stress. In addi-tion, it is difficult to create single spark erosion on a nonconductive ceramic workpiece as initial sparks are occurred between tool elec-trode and assisting electrode attached to workpiece. This paper presents the empirical factor for the estimation of spalling along with melting and vaporization through experimental study. Model of material removal rate as a function of capacitance and voltage are devel-oped in micromachining of nonconductive zirconium oxide (ZrO2) using (R-C) pulse type micro-EDM. The single spark erosion volume is derived from the fundamental principle of melting and vaporization. An empirical correction factor is introduced to compensate ran-dom spalling and multi-spark erosion effect.